2021
DOI: 10.1002/app.50903
|View full text |Cite
|
Sign up to set email alerts
|

4D printed stereolithography printed plant‐based sustainable polymers: Preliminary investigation and optimization

Abstract: The increasing demand for applying shape memory polymer to tissue culture and biomedical engineering has opened up research opportunities in the field of 4D Printing. The biocompatibility of the scaffolds as a culture medium resulted in the use of plant‐based polymers to provide an ambient environment for the growth of cells. This research investigates the 4D printing of acrylated epoxidized soybean oil (AESO), a plant‐based shape polymer. The objective of the present work is to establish the relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…6 Some of the applications of this method can be addressed to the automobile, electric, biomedical, and aerospace industries. [7][8][9] Parameters such as laser power distribution and scanning speed during construction, resin characteristics (such as monomers, oligomers, and curing agent compositions) can play a decisive role the maximum density of cross-linking and consequently final properties. 8,10 Generally, acrylates, vinyl ethers, and epoxides have been among the types of multifunctional monomers which were used for laser-induced polymerization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Some of the applications of this method can be addressed to the automobile, electric, biomedical, and aerospace industries. [7][8][9] Parameters such as laser power distribution and scanning speed during construction, resin characteristics (such as monomers, oligomers, and curing agent compositions) can play a decisive role the maximum density of cross-linking and consequently final properties. 8,10 Generally, acrylates, vinyl ethers, and epoxides have been among the types of multifunctional monomers which were used for laser-induced polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…This process consists of layer‐by‐layer polymerization of the photosensitive resin 6 . Some of the applications of this method can be addressed to the automobile, electric, biomedical, and aerospace industries 7–9 …”
Section: Introductionmentioning
confidence: 99%
“…An optimum clearance of 0.6 mm between sliding/moving surfaces is given between the components, and for the hand pressfitting of bearings and parts, clearance of 0.3 mm is adopted. Also, the material properties of ABS and PLA are considered for component manufacturing, considering their load-carrying capacity [21]. The literature review suggested that the average tensile strength of PLA is 56.6 MPa, and for ABS, it is 28.5 MPa.…”
Section: Project Demonstrationmentioning
confidence: 99%
“…With the current challenges, we are facing in terms of materials resources and pollution; there is an urgent need for more realistic ecological bio-based alternatives such as biopolymers; biocomposites, membrane and hydrogels. The cellulosic biomass derived from different natural resources offers a high potential to work as promising sustainable precursors for a cleaners and greener environment having advanced applications in water treatment, biomedical, soil remediation and pollution filtering to name a few using advanced synthesis and manufacturing techniques [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%